Evolution of physiological and haematological parameters with training load in elite male road cyclists: a longitudinal study - Zapico, A. G.; Calderon, F. J.; Benito, P. J.; Gonzalez, C. B.; Parisi, A.; Pigozzi, F.; Di Salvo, V. (The Journal of Sports Medicine and Physical Fitness, 2007)
Aim: The aim of this study was to describe and evaluate physiological parameters as a control tool for the monitoring of training in a group of elite cyclists during one season of training. Methods: The study is divided into two periods (winter or ''volume'' mesocycle and spring or ''intensity'' mesocycle) between the tests that they carried out in the laboratory, consisting of a ramp test to exhaustion (work load increases 25 W/·min) and a maximal lactate steady state (MLSS) test on a cycle ergometer. Macronutrients and hematological variables were recorded during the test periods as were the volume and the intensity of training sessions during the whole period of the study. Results: The physiological data were similar to those previously reported for professional cyclists (~450 Watts, ~78 mL/kg·min) and the values for the MLSS also agree with previous studies (~250 Watts). Subjects improved the first ventilatory threshold (VT1) (~52% to ~60% V.O2max) and the second ventilatory threshold (VT2) (~82% to ~87% V.O2max) after the first period of training even though its low intensity focused on the performance of VT1 (77% training in ''zone 1'', under VT1). The MLSS improved after the first period (~225 to ~250 Watts) and remained high in the second (~255 Watts). High levels of creatine kinase (~230 U/L) and urea (37 mg/L) were found, also a decrease in hemoglobin values (~15.4 to ~14.7g/dL). Conclusion: The high level reached by the subjects after the first period of training suggests that two effort tests could be enough to plan training. On the other hand, the decrease in some red blood cell and nutrition parameters suggests that there should be greater control over them during the season.